2022
DOI: 10.1097/fpc.0000000000000467
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic polymorphisms of pharmacogenes in Zimbabwe, a potential guide for the safe and efficacious use of medicines in people of African ancestry

Abstract: Objective Pharmacogenomics (PGx) is a clinically significant factor in the safe and efficacious use of medicines. While PGx knowledge is abundant for other populations, there are scarce PGx data on African populations and is little knowledge on drug-gene interactions for medicines used to treat diseases common in Africa. The aim of this study was to use a customdesigned open array to genotype clinically actionable variants in a Zimbabwean population. This study also identified some of the commonly used drugs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…In this study we could not verify clinical risk factors to be significant risk factors for developing DIC, of which previous studies have identified hypertension, female sex, age, cumulative anthracycline dose, as risk factors for DIC 3,14,27 . It may be possible that the small sample size in our study could have reduced the statistical power to demonstrate the significance of association of the clinical risk factors with DIC 12,[28][29][30][31][32][33] If we considered doxorubicin cumulative dose, we observe that there was no clear association between cumulative doxorubicin dose and cardiotoxicity (p = 0.357), which is not as expected 11,12,18,[34][35][36][37][38] . However, the high frequency (60.7%) of the cardioprotective variant could have influenced this dose relationship in our study.…”
Section: Discussionmentioning
confidence: 85%
“…In this study we could not verify clinical risk factors to be significant risk factors for developing DIC, of which previous studies have identified hypertension, female sex, age, cumulative anthracycline dose, as risk factors for DIC 3,14,27 . It may be possible that the small sample size in our study could have reduced the statistical power to demonstrate the significance of association of the clinical risk factors with DIC 12,[28][29][30][31][32][33] If we considered doxorubicin cumulative dose, we observe that there was no clear association between cumulative doxorubicin dose and cardiotoxicity (p = 0.357), which is not as expected 11,12,18,[34][35][36][37][38] . However, the high frequency (60.7%) of the cardioprotective variant could have influenced this dose relationship in our study.…”
Section: Discussionmentioning
confidence: 85%
“…Variant c.2846A>T is also a rare variant present across the general populations, American (0.30%), European (0.70%), South Asian (0.10%), African (0.08%) and Zimbabwe (0.29%). The frequency of the Hap B3 variant is high in the European (2.39%) and South Asian (1.90%) populations but low in other populations, American (0.60%) and African (0.08%) [15,26,27].…”
Section: Allele Frequency Of Dpyd Pathogenic Variants In the Guidelinesmentioning
confidence: 95%
“…PCR on the GenoPharm OpenArray panel following the manufacturer's protocol to detect normal and mutated alleles for CYP2D6. 26 Genotype calls were generated with the TaqMan Genotyper Software. The CYP2D6 copy number was determined using the Applied Biosystems TaqMan copy number variation (CNV) assays targeting exon 9 (assay ID: Hs00010001_cn) and the TaqMan copy number reference assay (ribonuclease P) as the reference gene.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from 200 μL of peripheral whole blood using the MagMAX DNA Multi‐Sample Ultra 2.0 Kit (ThermoFisher Scientific). Genotyping for CYP2D6 was performed using multiplex TaqMan PCR on the GenoPharm OpenArray panel following the manufacturer's protocol to detect normal and mutated alleles for CYP2D6 26 . Genotype calls were generated with the TaqMan Genotyper Software.…”
Section: Methodsmentioning
confidence: 99%